Supernumerary teeth vary depending on gender - Erika Calvano Küchler; Adriana Gomes da Costa; Marcelo de Castro Costa; Alexandre Rezende Vieira; José Mauro Granjeiro (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The presence of supernumerary teeth (ST) is a dental developmental anomaly of patterning and morphogenesis. Its variability of morphology, location and developmental timing can shed light on its etiology. In this work we report ST patterns. Orthopantomograms of 1,166 pediatric subjects were examined and the morphology, location and timing of the formation of ST were determined. The frequency of supernumerary teeth in the studied population was 2.3% (n = 27). Twenty-five subjects presented one ST. Maxilla midline was the most commonly affected region (nine cases). We noted high incidence of conical morphology in the midline region. Only teeth with tuberculate morphology presented delayed formation. ST in the midline region occurred more often in males whereas ST in the incisor region were more common in females. In conclusion, ST patterns vary depending on gender.